Pathology of sellar tumours: contemporary diagnostic approach: Pathology of sellar tumours: diagnostic approach - Manojlović Gačić, Emilija; Bosić, Martina; Zaletel, Ivan; Stojanović, Marko; Doknić, Mirjana; Pekić Đurđević , Sandra; Miljić, Dragana; Rašić, Dejan; Glumac, Sofija (Medical Research, 2023)
The sellar region is a complex area in the middle of the cranial base, with the pituitary gland in the central position and close anatomical association with crossroads of vital structures, making the basis for the development of numerous endocrinological and neurological conditions caused by the expansion or secretory activity of the tumour tissue. In this article, we will summarize the literature enclosing histopathological and immunohistochemical aspects of sellar tumours, together with clinical characteristics, leading to the proper diagnosis. A histopathological diagnostic algorithm will be presented for the most frequent tumours of this region, pituitary neuroendocrine tumours, as well as tumours of the posterior pituitary, meningiomas, craniopharyngiomas, chordomas, germ cell tumours haematological malignancies, Rathke cleft cyst and metastases. Contemporary histopathological diagnostic approach to sellar tumours strongly depends on the routine use of immunohistochemistry for a broad spectrum of antibodies, as well as detailed correlation with endocrinological, neurological, neurosurgical and neuroradiological aspects, which are mandatory for establishing an accurate diagnosis, reducing dilemmas and offering the best options for the further treatment of patients with sellar tumours.
Keywords: sellar tumour, pituitary neuroendocrine tumour, immunohistochemistry